Pertumbuhan Cacing Sutra (Tubifex sp) Pada Substrat Lumpur, Pasir, dan Kombinasinya - Allan Buddie Santoso; Kukuh Madyaningrana; Kisworo Kisworo (Florea : Jurnal Biologi dan Pembelajarannya, 2022)
The increase of freshwater aquaculture leads to the increasing demand for silkworms (Tubifex sp) as natural feed. Unfortunately, high demand of silkworm supply is not fully fulfilled yet because its availability is relied on natural catch. Cultivation of Tubifex sp. outside its natural habitats requires good information on substrates and feed. We aimed to study the effect of Â mud, sand and their combination use as substrates in supporting Tubifex sp growth. This study used complete randomized design with 5 treatments, namely K1 (100% sand), K2 (100% mud), P1 (combination 75% mud-25%) sand, P2 (combination 50% mud-50% sand), and P3 (combination 25% mud-75% sand) with triplicates on each treatment. Research was conducted for 21 days using fermented chicken manure as feed. Tubifex sp growth was measured on biomass, number of individuals, and average body weight, while pH, temperature, dissolved oxygen and total organic matter were listed as measured environmental parameters. The use of sand and mud combination as substrate was better than a single sand or mud alone to support Tubifex sp growth. Combination of 75% mud and 25% sand showed the best growth of Tubifex sp as observed on biomass value of 13,244 g, 370 number of individuals, and average weight body of 2,741 mg. The application of a combination of sand and mud substrates has a potency to support the cultivation of Tubifex sp outside its native habitat.